Plan de negocios para la creación de una unidad médica integral de diabetes en la ciudad de Ibarra - Palacios Cuadrado, Paúl Alexander (2015)
The Comprehensive Diabetes Medical Unit is a private health facility, specializes in the care, treatment and prevention of the diabetes, situated in the city of Ibarra, which is responsible for providing care and treatment services for patients with medical complications in other specialties generated from diabetes as cardiology, podiatry, ophthalmology and nutrition. The proxy service that delivers the Comprehensive Medical Unit is the packet of drugs distribution to diabetic patients. In the city of Ibarra there is not a specialize clinic that is dedicated to the comprehensive care of people with diabetes; this is the biggest opportunity that exploits the project and the main competitive advantage. However there are hospitals and clinics providing this service but not properly for the patients, making them indirect competition…